Perancangan dan Pembuatan Sistem Informasi Filing di Puskesmas Kalianget Kabupaten Sumenep - Ussisa Alattaqwa; Sustin Farlinda; Feby Erawantini; Bakhtiyar Hadi Prakoso (Universitas Duta Bangsa Surakarta, 2022)
Filing information system is an information system that can assist filing officers in controlling and controlling medical records with the scan qrcode feature to speed up the input process and can produce output in the form of reports and trackers. The medical record document storage system at the Kalianget Health Center, Sumenep regency often experiences missfiles (lost and misplaced) because the use of tracers and recording of entry and exit of medicalrecord documents is not implemented so that officers find it difficult to find and control these documents. The pupose of this study is to facilitate filing officers in control and control the entry and exit of medical record documents in order to minimize the occurrence of missfiles. The design of this information system uses the waterfall method and data collection through observation, interviews, documentation, and Focus Group Discussion. The programming language used is PHP and MySQL as the database, with Java Script as the template in this filing information system. The result of this study are in the form of a filing information system that can facilitate officers in finding, controlling and controlling the entry and exit of medical record documents.